2007
DOI: 10.1080/10428190601136163
|View full text |Cite
|
Sign up to set email alerts
|

Acute promyelocytic leukemia: A novelPML/RARαfusion that generates a frameshift in the RARα transcript and ATRA resistance

Abstract: Acute promyelocytic leukemia (APL) is characterized by increased promyelocytes in the marrow that harbor a t(15;17) and promyelocyte leukemia (PML)/RARalpha fusion gene. The oncogenic gene product is believed to act through disruption of the transcription-modulating function of RARalpha. Differentiation of promyelocytes and remission is achieved with all transretinoic acid (ATRA) therapy usually in combination with chemotherapy. This report describes a patient with the t(15;17) who did not respond typically to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Although ATRA is considered to be a relatively safe drug and more than 90% APL patients were reported to achieve CR [10], [11], drug resistances and side effects such as retinoic acid syndrome and psedudotumor cerebri can occur when using ATRA (PC) [12], [13]. Therefore, development of new drugs with higher efficacy and lower toxicity is still needed for APL treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although ATRA is considered to be a relatively safe drug and more than 90% APL patients were reported to achieve CR [10], [11], drug resistances and side effects such as retinoic acid syndrome and psedudotumor cerebri can occur when using ATRA (PC) [12], [13]. Therefore, development of new drugs with higher efficacy and lower toxicity is still needed for APL treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The dominant-negative effect of PML-RARa on RARa transcriptional regulation is unlikely to represent the full spectrum of effects mediated by PML-RARa and the reciprocal RARa-PML fusion transcripts. Indeed, a recent study identified a novel PML-RARa transcript lacking the functional domains of RARa in a patient who did not respond typically to ATRA treatment, suggesting that the effect of PML-RARa may be through interference of PML function (Zayed et al, 2007). The effects of RA may be also be attributed to its ability to alter DNA methylation, since treatment of APL blasts with RA led to reduced DNMT1, DNMT3A and DNMT3B expression and activity, associated with demethylation of RARb2 and differentiation of leukemic blasts (Fazi et al, 2005).…”
Section: Rara Translocations In Apl: Pml-rara As a Model For The Intementioning
confidence: 99%
“…The PML/RAR-α fusion protein has numerous functions in the process of leukemogenesis, but it also mediates response to all-trans retinoid acid (ATRA) therapy treatment 5 . Its oncogenic action, PML/RAR-α fusion protein expresses through disruption of both RAR-α and PML pathways 6,7 . PML/RAR-α exhibits its dominant negative impact on wild type RAR-α function as a transcriptional factor.…”
Section: Introductionmentioning
confidence: 99%